The Change of Production Process of Taohuawu New Year Prints and Its Application in Products - Liu, Peng; Sirisuk, Metta (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2025)
The objectives of this qualitative research were: 1) to study the changes in the production process of Taohuawu New Year prints, and 2) to analyze the application of Taohuawu New Year prints new production process in modern New Year print products. It uses literature research, field research, in-depth interviews, and participatory observation. The descriptive analysis method summarizes and discusses the results. The results were revealed as follows: 1) The changing times have led to the almost complete disappearance of traditional Taohuawu New Year print application occasions. Concurrently, the continuous emergence of new materials and technologies has greatly impacted New Year prints. Traditional Taohuawu New Year print production involves manual skills and artistic charm, but modern tools, materials, and technologies have greatly altered it. This transformation has improved efficiency, enriched forms, and prompted reflection on the balance of tradition and modernity. And 2) the modern Taohuawu New Year print production process has opened new product application possibilities. Participatory new products prioritizing consumer experience have successfully integrated Taohuawu New Year prints into contemporary humanistic life, promoting their inheritance and development.